2007
DOI: 10.1002/bit.21761
|View full text |Cite
|
Sign up to set email alerts
|

Determination of diffusion coefficients and diffusion characteristics for chlorferon and diethylthiophosphate in Ca‐Alginate gel beads

Abstract: Diffusion characteristics of chlorferon and diethylthiophosphate (DETP) in Ca-alginate gel beads were studied to assist in designing and operating bioreactor systems. Diffusion coefficients for chlorferon and DETP in Ca-alginate gel beads determined at conditions suitable for biodegradation studies were 2.70 x 10(-11) m(2)/s and 4.28 x 10(-11) m(2)/s, respectively. Diffusivities of chlorferon and DETP were influenced by several factors, including viscosity of the bulk solution, agitation speed, and the concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Previous reports have suggested that this higher productivity results from cellular or genetic modifications induced by immobilization. There is evidence indicating that immobilized cells are much more tolerant to perturbations in the reaction environment and less susceptible to toxic substances, which makes immobilized cell systems particularly attractive for the treatment of toxic substances like pesticides (Ha et al 2008). In addition, the enhanced degradation capacity of immobilized cells is due primarily to the protection of the cells from inhibitory substances present in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have suggested that this higher productivity results from cellular or genetic modifications induced by immobilization. There is evidence indicating that immobilized cells are much more tolerant to perturbations in the reaction environment and less susceptible to toxic substances, which makes immobilized cell systems particularly attractive for the treatment of toxic substances like pesticides (Ha et al 2008). In addition, the enhanced degradation capacity of immobilized cells is due primarily to the protection of the cells from inhibitory substances present in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…(19) and simulated in MATLAB 7.0. For the bead diameters, the simulation results revealed that the mass transfer ceased beyond 77% radius for the 0.20 cm bead after 62 h, 69% radius for the 0.4 cm bead after 54 h, 54% radius for the 0.6-cm bead after 47 h and 43% radius for 0.8-cm bead after 12 h. Hence, the dynamics of the mass transfer rate within the entire biocatalyst diameters at an optimum location of 60% biocatalyst radii (0.6 r) until an optimum time period of 20 hours were monitored so that the mass transfer rate completely prevailed in the study range and the results are depicted in Figs.…”
Section: Dynamics In Mass Transfer Rate Within the Biocatalystmentioning
confidence: 99%
“…Recently, the influence of mass transfer resistance on formaldehyde degradation in kissirisimmobilized R. eutropha has been reported [18]. Ha and his group [19] studied the diffusion characteristics of chlorferon and diethylthiophosphate in Ca-alginate gel beads. The internal mass transfer limitations of phenol biodegradation using Ca-alginate-immobilized P. putida beads in a batch system have been reported, and a literature review presented of the effective diffusion coefficient and effectiveness factor along with Thiele's modulus [20].…”
Section: Introductionmentioning
confidence: 99%
“…Goncalves et al [18] concluded that external diffusion was not significant when the stirring speed is higher than 400 rpm in their work in which they studied influence of mass transfer limitations on the enzymatic synthesis of ␤-lactam antibiotics catalyzed by penicillin G acylase immobilized on glioxil-agarose. Based on Biot number calculations, Calcium-alginate gel beads were not subject to external mass transfer resistances in the diffusion experiments of chlorferon and diethyl thiophosphate in Ca-alginate gel beads [19]. Effect of the external mass transfer was neglected when the rotating speed was greater than 200 rpm [20].…”
Section: Effect Of Internal and External Diffusionmentioning
confidence: 99%
“…Chen and Tsai [17] conducted that the effect of internal diffusion on the enzymatic reaction was neglected in an enantioselective synthesis of (S)-ibuprofen ester prodrug by immobilized C. rugosa lipase with particle size <1 mm, pore size 0.05-0.5 m. In the synthesis of antibiotics catalyzed by immobilized penicillin G acylase, no intraparticle diffusion limitation was affecting the system when enzyme load was kept lower [18]. Using calcium-alginate gel beads with radii of 1.65-1.70 mm, effectiveness factors indicated that internal mass transfer resistance was negligible [19], therefore, the degradation rates of chlorferon and DETP inside Ca-alginate gel beads were reaction-limited. Using Novozym 435 particles with diameter of 0.6 mm, the Thiele modulus,˚was calculated to be 0.017, which indicated that internal mass transfer limitation could be neglected [20].…”
Section: Effect Of Internal and External Diffusionmentioning
confidence: 99%